Culturally Responsive Clay Modeling Interventions: Improving Fine Motor Skills and Cultural Connection in Slow Learner Children - Karsini, Karsini; Suparno, Suparno (Papanda Publisher, 2025)
Fine motor skills development presents significant challenges for slow learners in early childhood education. This study investigated the effectiveness of local wisdom-based play methods using geometric clay modeling activities to enhance fine motor skills among slow learner children in kindergarten settings. A collaborative classroom action research design following the Kemmis and McTaggart model was implemented across three cycles at State Kindergarten 1, Long Mesangat District. Five male participants aged 5-6 years, identified as slow learners with fine motor difficulties, engaged in structured clay modeling activities incorporating traditional geometric patterns. Data collection utilized systematic observations with validated checklists assessing five domains: hand dexterity, eye-hand coordination, muscle strength, cultural integration, and motivation levels. Performance was evaluated using four developmental categories from